STRATEGI INOVASI DAN BRANDING UMKM ES TELER KUY DI DESA SUKAMAJU KECAMATAN BAREGBEG KABUPATEN CIAMIS - Ikmal Mumtahaen; Dinar Indrayana (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study analyzes the product innovation and branding strategies of Es Teler Kuy MSMEs in increasing business competitiveness in Sukamaju Village, Baregbeg District, Ciamis Regency. The purpose of this study is to examine the application of product innovation and strengthening brand identity as an effort to expand the market and maintain business sustainability. The method used is qualitative research with a case study approach through in-depth interviews, observation, and documentation, with data analysis using the Miles and Huberman model. The results show that innovation is carried out through the transformation of traditional es teler into a modern dessert with a creamy sauce, the use of premium fruit, a variety of toppings, and biodegradable packaging that increases consumer appeal and drives an increase in demand of up to 40%. Branding strategies are built through a locally distinctive visual identity, memorable slogans, and the use of consumer-driven social media to expand market reach and strengthen product image. The impact is seen in increased sales, price affordability, and socioeconomic contributions in the form of job creation and strengthening village economic identity. However, limited distribution and low digital literacy remain obstacles. This study confirms that the integration of product innovation and contextual branding effectively increases the competitiveness of rural MSMEs